2014
DOI: 10.1016/j.jcyt.2013.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Human adipose-derived mesenchymal stromal cell pigment epithelium–derived factor cytotherapy modifies genetic and epigenetic profiles of prostate cancer cells

Abstract: Background aims Adipose-derived mesenchymal stromal cells (ASCs) are promising tools for delivery of cytotherapy against cancer. However, ASCs can exert profound effects on biological behavior of tumor cells. Our study aimed to examine the influence of ASCs on gene expression and epigenetic methylation profiles of prostate cancer cells as well as the impact of expressing a therapeutic gene on modifying the interaction between ASCs and prostate cancer cells. Methods ASCs were modified by lentiviral transducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Findings from other oncological models highlight excess adiposity-associated impact in methylation markers known to associate with potential effect in the cancer microenvironment (e.g., aromatase, prostaglandin E 2 receptor in breast cancer) [ 34 , 35 ]. Obesity has also been shown to associate with methylation of cancer-related genes (E-cadherin, p16, and RAR-β(2)) directly in malignant breast cells [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Findings from other oncological models highlight excess adiposity-associated impact in methylation markers known to associate with potential effect in the cancer microenvironment (e.g., aromatase, prostaglandin E 2 receptor in breast cancer) [ 34 , 35 ]. Obesity has also been shown to associate with methylation of cancer-related genes (E-cadherin, p16, and RAR-β(2)) directly in malignant breast cells [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The human prostate cancer cell line PC3 was obtained from American Type Culture Collection and maintained in 10% fetal bovine serum (FBS, Fisher) in Roswell Park Memorial Institute medium 1640 (RPMI, Corning). ASCs from two male Caucasian donors, generously provided by J. Gimble (Tulane University), were collected as previously described ( Zolochevska et al 2014 ) and cultured on fibronectin-coated plasticware in modified media conditions that have been described previously ( Ruiz et al 2010 ). ASCs from Donor 1 were isolated from midsection liposuction, and Donor 2 ASCs were isolated from liposuction samples from breast tissue.…”
Section: Methodsmentioning
confidence: 99%
“…It is thought that these cell types are recruited into tumors to promote healing and to potentially quell the inflammatory response ( Aggarwal and Pittenger 2005 ; González et al 2009 ). Although many investigators, including ourselves, are utilizing ASCs as a potential therapeutic modality because of their inherent tropism towards tumors ( Hall et al 2007 ; Zolochevska et al 2014 ), emerging evidence has suggested that endogenous ASCs may also play a critical role in tumor progression depending on the cellular context ( Barron and Rowley 2012 ; Kidd et al 2012 ). Moreover, the potential effects of environmental toxicants such as iAs on these endogenous cells is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells are a type of adult stem cell with the attributes of self-renewing and multipotency. They can be used in biomedical research, new drug development, and toxicology studies, and so forth [ 1 ]. Currently this type of cell is a focal point in clinical research and application [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%